ANALISIS CATCHMENT AREA TERHADAP TINGGALAN MOLUSKA GUA - Muhamad Ardian Syah; Abdul Rauf Suleiman; Syahrun Syahrun (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research examines archaeological remains in the form of mollusks found at the Gua Tengkorak 2 site in Wawontoaho Village, Wiwirano District, North Konawe Regency. The methods used in this study include mollusk taxonomy analysis and catchment area analysis. Based on the taxonomic analysis, 11 species of mollusks from three different habitats were identified: one species of terrestrial gastropod (Cyclotus Politus), seven species of freshwater gastropods (Tylomelania Celebicola, Tylomelania Palicolarum, Tylomelania Perfecta, Tylomelania Sarasinorum, Tylomenia Scalariopsis, Tylomelania Sp, and Tylomelania Wallacei), two species of marine gastropods (Olividae and Tarebia Granifera), and one species of marine bivalve (Cytherea Incrassata). The catchment area for freshwater mollusks is the Larambe River, a freshwater environment located 4 kilometers from Gua Tengkorak 2. Meanwhile, the catchment area for marine mollusks is the southeastern region of North Konawe Regency, located approximately 20.5 kilometers from Gua Tengkorak 2. Specifically, no search for the catchment area of the terrestrial mollusk (Cyclotus Politus) was conducted due to significant environmental changes.